Sosialisasi Penggunaan Dampak Penggunaan Pupuk dan Pestisida Kimia Di Desa Karangrejo Oleh KKN UMD Dalam Upaya Peningkatan Kesadaran dan Kelestarian Lingkungan - Azzahro, Firyal Nurul Haifa; Habibie, Muhammad; Setiawan, Moh Rizqi; Safira, Arlinda; Safitri, Berliana Desta; Wirayudo, Haykal FIkram; Khozin, Mohammad Nur (Universitas Mataram, 2024)
The majority of residents in the village of Karangrejo work as farmers and breeders. Yosowilangun sub-district has an area of ​​2,271 hectares of dry land and 56,206 hectares of paddy fields. The problem in Karangrejo village is the lack of awareness of the people who dispose of livestock manure carelessly without any use. In addition, another problem is that some Karangrejo farmers use chemical fertilizers which are currently experiencing price increases and the government has also reduced subsidies. Therefore, UMD Community Service Students at Jember University Group 197 together with UPT BPP Yosowilangun carried out an innovative program to socialize the impact of using chemical fertilizers and pesticides. This aims to reduce the use of chemical fertilizers and pesticides and make farmers and breeders aware of efforts to create environmentally friendly villages. This service activity was carried out through socialization and distribution of pre-test and post-test questionnaires. The method used is quantitative by distributing questionnaires to Karangrejo farmers. Based on the results of the questionnaire data analysis, it can be seen that there is an increase in farmers' knowledge regarding the advantages of using organic fertilizers and plant-based pesticides and the impact of using chemical fertilizers and pesticides. This is expected to be able to make people aware of the dangers of using chemical fertilizers and pesticides that can damage the surrounding environment.